Intracranial Arterial Calcifications: Potential Biomarkers of Stroke Risk and Outcome - Fote, Gianna M.; Raefsky, Sophia; Mock, Kelton; Chaudhari, Amit; Shafie, Mohammad; Yu, Wengui (Frontiers in Neurology, 2022)
Intracranial artery calcifications (IAC), a common and easily identifiable finding on computed tomorgraphy angiography (CTA), has gained recognition as a possible risk factor for ischemic stroke. While atherosclerosis of intracranial arteries is believed to be a mechanism that commonly contributes to ischemic stroke, and coronary artery calcification is well-established as a predictor of both myocardial infarction (MI) and ischemic stroke risk, IAC is not currently used as a prognostic tool for stroke risk or recurrence. This review examines the pathophysiology and prevalence of IAC, and current evidence suggesting that IAC may be a useful tool for prediction of stroke incidence, recurrence, and response to acute ischemic stroke therapy.